Constructing and Validating the Spiritual Justice Scale: A Psychometric Study - Demir, Yasin; Okan, Nesrullah; Pekdemir, Sevket (Springer, 2026)
The objective of this study was to develop and validate the Spiritual Justice Scale (SJS) as a reliable measure of individuals' perceptions of spiritual justice. The development of the scale was founded upon theoretical foundations and supported by rigorous statistical analyses. Exploratory factor analysis revealed a one-dimensional structure explaining 56.26% of the variance, while confirmatory factor analysis confirmed the model with acceptable fit indices. Reliability analysis demonstrated high internal consistency (Cronbach's alpha = 0.95). Furthermore, a significant positive correlation was identified between the SJS and the Toronto Empathy Questionnaire (r = 0.42, p < 0.001), suggesting a close relationship between spiritual justice and compassion, as well as fairness. The findings suggest that the SJS is a psychometrically sound instrument. Its potential applications extend to research and practice in counselling, education, social work, and spirituality studies, offering a foundation for further investigations into the role of spiritual justice in psychological well-being and social functioning.
Keywords: Spiritual justice; Validity; Reliability; Scale development; Spirituality and mental health